Comparison of Administrative Court Systems between Diwan al-Mazhalim in Saudi Arabia and State Administrative Courts in Indonesia - Siti Mardiyah (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study aims to examine and compare the administrative justice systems of the Diwan al-Mazhalim in Saudi Arabia and the Administrative Court (PTUN) in Indonesia to understand how Islamic law and modern legal frameworks shape judicial governance. Using the theory of comparative law and legal system theory as analytical foundations, the research employs a qualitative-descriptive approach through a comprehensive review of constitutional texts, statutory laws, and scholarly literature. The analysis reveals that the Diwan al-Mazhalim, operating under the direct authority of the King, embodies a theocentric system grounded in Sharia principles, prioritizing moral and religious dimensions of justice. Conversely, Indonesia’s State Administrative Courts reflects a state-centered legal system based on constitutionalism and the rule of law, emphasizing legality, procedural fairness, and good governance. The findings highlight that while both institutions aim to safeguard citizens’ rights and ensure administrative accountability, they differ in their philosophical foundations and institutional orientations. The study contributes to comparative administrative law by providing a conceptual framework for harmonizing Islamic ethical principles with modern administrative justice, offering valuable insights for reforming legal systems in Muslim-majority countries seeking balance between divine law and state regulation.